Budaya Dosen Untuk Mendidik Karakter Mahasiswa PGSD - Wahyu, Karina; Anita, Novi; Nur, Adyllah; Nurcahyo, Imam; Mumtahanah, Mumtahanah; Ilmi, Afra (Elementary Education Journal, 2023)
Background: In this fast-changing era, the character building of PGSD students is an important part of their preparation to become good teachers. The role of the teacher as a guide and role model for students is crucial in this process. PGSD's struct culture trains student character through customs and beliefs, important in sustainable character education. Reflects the faculty's commitment in preparing students to lead social change with a strong spirit and character. Method: Ethnographic research is needed to examine the culture of character building for PGSD lecturers and students. The ethnographic approach focuses on in-depth observation and interviews with teachers and PGSD students to analyze their social interactions. According to research, teacher culture has a significant impact on student character development. Result: This study shows that the use of traditional culture and beliefs in the education of PGSD lecturers has a positive effect on the development of student personality in learning. The character of PGSD students shows how important it is to recognize local culture in education and support the preservation of local traditions and wisdom. Confident teachers encourage students with character. This study is about how important traditional culture is for PGSD students. Indigenous culture and beliefs impact the environment, student personality, and ethnographic research. Confident teachers encourage students with character. Implication: This study is about how important traditional culture is for PGSD students. Indigenous culture and beliefs impact the environment, student personality, and ethnographic research. Confident teachers encourage students with character. This study is about how important traditional culture is for PGSD students. Indigenous culture and beliefs impact the environment, student personality, and ethnographic research Novelty: The present study revealed the implementation of traditional culture is for PGSD students.